Comparative study on tribological behavior of CrAlN coating in atmosphere, deionized water and 5 wt% NaCl solution. (15th October 2019) - Wen, Ping; Zhang, Fan; Chen, Yubo; Guo, Shengda; Zhou, Shengguo; Ye, Yuwei; Chen, Hao
Abstract: CrAlN coating was prepared by magnetron sputtering technology on the surface of 304 stainless steel and silicon wafer. The microstructure and composition of CrAlN coating were characterized by scanning electron microscopy (SEM), x-ray diffraction (XRD), x-ray photoelectron spectrometer (XPS) and atomic force microscope (AFM). The anti-friction and anti-wear properties of CrAlN coating in ambient air, distilled water and 5 wt% NaCl solution were investigated by wear tester. The results showed that the CrAlN coating was mainly composed of CrN, Cr2 N and AlN phases, indicating that fractional Cr atoms in the CrN lattice were replaced by Al atoms. The friction coefficients of CrAlN coating in distilled water and 5 wt% NaCl solution were about 0.39 and 0.41, which was reduced by 48.0% and 45.3% compared with ambient air, respectively. In the case of wear rate, the CrAlN coating exhibited the lowest value of 0.58 × 10 −15 m 3 Nm −1 in distilled water and the highest value of 3.28 × 10 −15 m 3 Nm −1 in ambient air.